Observation of elastic spin with chiral meta-sources - Weitao Yuan (Nature Portfolio, 2021)
’Following up on the recent theoretical demonstration here the authors bring us a step closer to the real implementation of efficient ultrasonic chiral sources. They experimentally demonstrate the presence of elastic spin waves, Rayleigh and Lamb waves, generated by a chiral-meta source, characterizing their basic properties.